Project Report on PIC Based Interprocessor Communication for Train Actuated Warning System - RAKESH R, GURURAJ M V and RAGHU G S (2004)
INTERNAL GUIDE: A ARAVIND, MVJCE EXTERNAL GUIDE: DEEPAK K, GG TRONICS
Keywords: Train Actuated Warning System